Kidney injury associated with COVID-19 infection and vaccine: A narrative review - Pacheco, Iago Carvalho Rezende; Costa, Denise Maria do Nascimento; Sousa, Deborah Serra; Salgado Filho, Natalino; Silva, Gyl Eanes Barros; Neves, Precil Diego Miranda de Menezes (Frontiers in Medicine, 2022)
The respiratory tract is the main infection site for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), resulting in many admissions to intensive care centers in several countries. However, in addition to lung involvement, kidney injury caused by the novel coronavirus has proven to be a significant factor related to high morbidity and mortality, alarming experts worldwide. The number of deaths has drastically reduced with the advent of large-scale immunization, highlighting the importance of vaccination as the best way to combat the pandemic. Despite the undeniable efficacy of the vaccine, the renal side effects associated with its use deserve to be highlighted, especially the emergence or reactivation of glomerulopathies mentioned in some case reports. This study aimed to identify the main renal morphological findings correlated with COVID-19 infection and its vaccination, seeking to understand the pathophysiological mechanisms, main clinical features, and outcomes.